Feasibility study and cell design for performing local electrochemical impedance spectroscopy measurements using an atomic force microscopy set-up. (10th August 2017) - Muselle, Thibault; Simillion, Hans; Van Laethem, Dries; Deconinck, Johan; Hubin, Annick
Abstract: This paper studies the feasibility of performing Local Electrochemical Impedance Spectroscopy (LEIS) and Atomic Force Microscopy (AFM) within a single set-up, using a hybrid probe. The geometry of the set-up along with the extremely small size of the probe used is expected to result in distorted impedances and very low potentials, respectively. Numerical simulations using a multi-ion transport and reaction model (MITReM), show that the distortions can be mathematically corrected for and that our electronic equipment is capable of measuring the minute potentials.